AB0866 METABOLIC SYNDROME IN PATIENTS WITH GOUT ATTENDED IN A SPECIALIZED OUTPATIENT UNIT IN SPAIN. COMPARISON WITH GENERAL POPULATION AND CARDIOVASCULAR IMPLICATIONS. (June 2019) - Calvo-Aranda, Enrique; Sanchez-Aranda, Fernando Manuel; Cebrian, Laura; Matias de la Mano, Maria Angeles; Garcia-Lorenzo, Elena; Navio Marco, Maria Teresa
Abstract : Background: Metabolic syndrome (MS) is a cluster of interrelated components: central adiposity or higher waist circumference (WC), high values of triglycerides (TG), elevated blood pressure (BP), impaired fasting glucose and decreased HDL-cholesterol (HDL-c). It is associated with a higher incidence of developing diabetes (DM), as well as with other cardiovascular diseases (CVD). A direct relationship between serum uric acid (sUA) and the risk of develop MS has been reported in several studies of patients with hyperuricemia and gout. Objectives: To study the prevalence of MS and associated CVD in patients with gout attended in a specialized outpatient unit, comparing with other local and national studies. Methods: Retrospective observational study with consecutive patients diagnosed with gout according to EULAR/ACR criteria between August and December 2018. We analyzed the presence of MS according to the 2015 International Diabetes Federation criteria (central obesity as BMI ≥30 kg/m2 or WC ≥94 cm (≥80 in women), with ≥2 of the following: TG ≥1.71 mmol/l, HDL-c <1.04 mmol/l (<1.3mmol/l in women), hyperglycemia ≥5'55 mmol/l (or T2DM previously diagnosed or hypoglycaemic treatment), hypertension (HT; ≥130/85 mmHg or use of antihypertensive drugs). Treatments received and family history (FH) of gout an CVD were recorded. Demographic, anthropometric, clinical and analytical variables were analyzed. All data were compared with those obtained in three Spanish studies of the general population: DARIOS, ENRICA, SIMETAP. Results: 57 patients with gout were included. Average age 62 years (39-90), 48 years (18-90) at the time of gout onset. 94.7% males. 40.3% with FH of gout, tophi in 52.6%. Clinical pattern: monoarticular 15.8%, oligoarticular 56.1%, polyarticular 28.1%. 68.4% received urate-lowering therapy: 45.6% Allopurinol, 22.8% Febuxostat. SUA at the time of inclusion 6.7 mg/dl (2.6-11.3). Total cholesterol 186 mg/dl (4.84 mmol/l; 96-350 mg/dl/2.5-9.1 mmol/l). TG 185 mg/dl (2.11 mmol/l; 68-742 mg/dl/0.78-8.46 mmol/l). BMI 31.8 kg/m2 (24-58.1). MS was found in 66.7% and premorbid metabolic syndrome (pMS; excluding patients with previously diagnosed CVD or DM) in 26.3%. Obesity 57.9% and overweight 38.6%. HT 80.7%; 10.5% diagnosed in our unit. DM 22.8%. Dyslipidemia (DL: hypercholesterolemia or high levels of TG) 64.9%; 14% diagnosed in our unit. 29.8% smokers, 49.1% formers. Alcohol consumers 54.4%. Chronic kidney disease (CKD) 42.1%; 12.3% diagnosed in our unit. Ischemic heart disease (IHD) 14%. Stroke 24.6%. FH of CVD 24.6%. Comparing with the general population the prevalence of MS and pMS was higher (DARIOS: 31% and 24%, respectively; ENRICA: 22.7% and 16.9%; SIMETAP: 41% and 25%), as well as with the presence of CKD (11.5% in SIMETAP) and CVD (SIMETAP: HT 38%, T2DM 16%, obesity 28%, IHD 4.8% and stroke 3.8%). Conclusion: There is a very significant percentage of MS and pMS in patients with gout compared to the general population, with important presence of CKD and CVD, sometimes underdiagnosed. Nursing guidelines were established with healthy lifestyle and periodic controls directed at all patients, with special emphasis on those newly diagnosed of HT or DL, as well as those of higher cardiovascular risk. References: [1] Fernández-Bergés D, et al. Metabolic syndrome in Spain: prevalence and coronary risk associated with harmonized definition and WHO proposal. DARIOS study. Rev Esp Cardiol. 2012;65(3):241-8 [2] Guallar-Castillón P, et al. Magnitude and management of metabolic syndrome in Spain in 2008-2010: the ENRICA study [3] Ruiz-García A, et al. Population and methodology of the SIMETAP study: Prevalence of cardiovascular risk factors, cardiovascular diseases, and related metabolic diseases. Clin Investig Arterioscler. 2018;30(5):197-208 Disclosure of Interests: Enrique Calvo-Aranda Speakers bureau: Grühnental, SOBI, Menarini, fernando manuel sanchez-aranda: None declared, Laura Cebrian: None declared, maria angeles matias de la mano: None declared, elena garcia-lorenzo: None declared, maria teresa navio marco: None declared